Examining the Impact of Corporate Social Responsibility on Brand Loyalty in Emerging Markets - Rina Aisyah; Amirul Faiz (International Journal of Economics, Management and Accounting, 2024)
This paper explores the role of Corporate Social Responsibility (CSR) in building brand loyalty among consumers in emerging markets. Using case studies from companies in Latin America and Southeast Asia, the research analyzes how CSR initiatives influence consumer perceptions, trust, and loyalty. The study finds that effective CSR programs can enhance brand loyalty, particularly among socially conscious consumers, providing valuable insights for companies operating in emerging economies.